TNFα stimulates osteoclastogenesis and expression of CX3CL1 in non-adherent bone marrow cells - Yuto Otsuka; Narumi Hattori; Hiromasa Aoki; Kohki Toriuchi; Yasumichi Inoue; Hidetoshi Hayashi; Gen Kuroyanagi; Yohei Kawaguchi; Yuko Waguri-Nagaya; Mineyoshi Aoyama (Biochemistry and Biophysics Reports)
The balance between bone formation by osteoblasts and bone resorption by osteoclasts is a critical step in maintaining bone homeostasis. Excessive activation of osteoclasts is important in the bone destruction seen in diseases such as osteoporosis and rheumatoid arthritis. The microenvironment around bone marrow cells regulates osteoclastogenesis through cytokine expression. Tumor necrosis factor–α (TNFα) is a proinflammatory cytokine that plays an important role in bone loss in rheumatoid arthritis. Therefore, this study investigated the effect of TNFα on osteoclastogenesis via chemokines produced by microenvironmental cells. In in vitro culture of mouse bone marrow cells, TNFα added simultaneously with receptor activator of nuclear factor kappa-B ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) from the initiation of culture significantly inhibited osteoclast formation. By contrast, TNFα stimulation from 7 days after prior stimulation with RANKL and M-CSF significantly promoted osteoclastogenesis. This late-stage promotional effect was associated with the upregulation in non-adherent bone marrow cells of C-X3-C motif chemokine ligand 1 (CX3CL1) and C-X-C motif ligand 7 (CXCL7), which are potent chemoattractant and adhesion molecules. Neutralizing antibodies against TNF receptor 1 (TNFR1) and TNFR2 markedly suppressed osteoclastogenesis in the presence of TNFα. Additionally, these antibodies significantly reduced CX3CL1—but not CXCL7—mRNA expression levels in non-adherent bone marrow cells. In conclusion, our results suggest that TNFα treatment in the late stage promotes osteoclast formation and increases the expression of CX3CL1 in non-adherent bone marrow cells. These findings highlight the time-dependent role of TNFα in osteoclastogenesis relative to non-adherent bone marrow cells.